1989
DOI: 10.1007/bf00393696
|View full text |Cite
|
Sign up to set email alerts
|

Glucose excretion by the symbiotic Chlorella of Spongilla fluviatilis

Abstract: Abstract. C7?/3n?//<3 ^r^Ar/v?/^^ strain 211-40c, a symbiotic C/z/orf//df isolated from a freshwater sponge, excreted between 3% and 5% of assimilated ^C02 as glucose in the light, with a pH optimum around 5. This percentage increased when the illuminance was lowered (to 15% at 200 lx). Release of [*^C]glucose continued in the dark and could be inhibited by the uncoupler carbonyl cyanide /7-trifluoromethoxyphenylhydrazone (FCCP). Net efflux of glucose occurred even at a concentration ratio of extracellular/int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Such findings support earlier more circumstantial evidence for glucose transfer (Trench et al, 1978;Kremer et al, 1979). Effective glucose transfers are known for erythrocytes (Le Fevre, 1959) and for the symbiotic Chlorella of Spongillafluuiatilis (Fischer et al, 1989). A translocation of glucose was also described in chloroplasts (Schafer et al, 1977).…”
Section: Discussionsupporting
confidence: 87%
“…Such findings support earlier more circumstantial evidence for glucose transfer (Trench et al, 1978;Kremer et al, 1979). Effective glucose transfers are known for erythrocytes (Le Fevre, 1959) and for the symbiotic Chlorella of Spongillafluuiatilis (Fischer et al, 1989). A translocation of glucose was also described in chloroplasts (Schafer et al, 1977).…”
Section: Discussionsupporting
confidence: 87%
“…Small yields of extracellular sugars have been reported for certain C. sorokiniana strains previously, but these amounts were quite low (and were found during cultivation at pH ~2.5) in comparison to those produced by M. conductrix SAG 241.80, and the analysis of sugar from this previous report was done by first growing cells in a standardized medium and then transferring to a citrate‐phosphate buffer to determine sugar production over a broader pH range (Kessler et al ., ). In contrast, a green alga identified as C. sorokiniana strain 211‐40c isolated from the freshwater sponge S. fluviatilis was reported to release elevated levels of extracellular sugar in the form of glucose, with a maximum production in the pH range of 4.5–5.5 (Fischer et al ., ), indicating that simple naming designations are not necessarily a good benchmark for determining whether a specific strain should or should not release extracellular sugars in substantial quantities. Determinations of sugar production by any other strains besides the two strains sequenced and annotated here fell outside the scope of this study, though the potential for sugar production in some of these alternative strains listed in Figure is noted here.…”
Section: Resultsmentioning
confidence: 99%
“…Green algae can also form associations with aquatic species, and are prominent among symbiotic algae strains that form close associations with ciliates such as Paramecium bursaria , the heliozoan Acanthocystis turfacea , the freshwater sponge Spongilla fluviatilis , and invertebrates such as the hydroid polyp Hydra viridis (Fischer et al ., ; Hoshina et al ., ; Pröschold et al ., ). In some cases, these symbiotic algae have developed such close associations with their hosts that they are unable to survive outside of the host relationship (Bosch, ).…”
Section: Introductionmentioning
confidence: 98%
“…The present study showed that cyanelles, with respect to their carrier composition, are as tightly incorporated into eukaryotes as organelles. This is in contrast to Chlorella symbioses where either maltose (in the case of Paramecium bursaria, Ziesenisz et al, 1981) or glucose (with Spongillajluviatilis, Fischer et al, 1989) are the major transport forms. As the Pj-translocator has hitherto been described only for cyanelles in organisms of a low evolutionary scale, comparisons with plastids from algal groups cannot be drawn as yet.…”
Section: Discussionmentioning
confidence: 75%